2009
DOI: 10.1099/vir.0.008243-0
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the level of RNA silencing suppression caused by triple gene block protein 1 (TGBp1) from various potexviruses during infection

Abstract: RNA silencing is an important defence mechanism against virus infection, and many plant viruses encode RNA silencing suppressors as a counter defence. In this study, we analysed the RNA silencing suppression ability of multiple virus species of the genus Potexvirus. Nicotiana benthamiana plants exhibiting RNA silencing of a green fluorescent protein (GFP) transgene showed reversal of GFP fluorescence when systemically infected with potexviruses. However, the degree of GFP fluorescence varied among potexviruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 53 publications
2
65
0
2
Order By: Relevance
“…TGBp1 suppresses S-RNAi but not IR-RNAi (Senshu et al, 2009). This is consistent with the finding that TGBp1 inactivates SGS3/RDR6-mediated dsRNA synthesis because SGS3 and RDR6 are only involved in S-RNAi, but AGO1 and DCL4 are involved in both S-RNAi and IR-RNAi.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…TGBp1 suppresses S-RNAi but not IR-RNAi (Senshu et al, 2009). This is consistent with the finding that TGBp1 inactivates SGS3/RDR6-mediated dsRNA synthesis because SGS3 and RDR6 are only involved in S-RNAi, but AGO1 and DCL4 are involved in both S-RNAi and IR-RNAi.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, in the TGBp1 transgenic plants, the levels of tasiRNA were significantly reduced ( Figure 1C; Supplemental Table 2), and the levels of tasiRNA target mRNA increased ( Figure 1D). Although previous reports have indicated that PVX-TGBp1 transformants do not exhibit any visible developmental abnormalities (Dunoyer et al, 2004), this may be due to the low level of suppressor activity of PVX TGBp1 (Senshu et al, 2009).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations